2021
DOI: 10.1002/eji.202048900
|View full text |Cite
|
Sign up to set email alerts
|

c‐Rel employs multiple mechanisms to promote the thymic development and peripheral function of regulatory T cells in mice

Abstract: The NF‐κB transcription factor c‐Rel is a critical regulator of Treg ontogeny, controlling multiple points of the stepwise developmental pathway. Here, we found that the thymic Treg defect in c‐Rel‐deficient (cRel–/–) mice is quantitative, not qualitative, based on analyses of TCR repertoire and TCR signaling strength. However, these parameters are altered in the thymic Treg‐precursor population, which is also markedly diminished in cRel–/– mice. Moreover, c‐Rel governs the transcriptional programme of both th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 109 publications
0
6
0
Order By: Relevance
“…In contrast to animals with systemic c-Rel deficiency, mice with conditional deletion of c-Rel in Treg cells develop signs of inflammation with age, and c-Rel-deficient Treg cells are unable to control pathogenic T cells in a T cell transfer colitis model [ 26 ], demonstrating a role for c-Rel in Treg cell–mediated immune control. This was also observed in cell transfer experiments which showed that c-Rel knockout Treg cells are deficient in controlling the expansion of wild-type T cells in lymphopenic hosts [ 22 ]. Along the same line, conditional ablation of c-Rel in Treg cells affects a distinct set of genes (around 300 are up- and 350 downregulated) [ 26 ].…”
Section: Canonical Nf-κb Transcription Factors and Treg Cell Functionmentioning
confidence: 71%
See 2 more Smart Citations
“…In contrast to animals with systemic c-Rel deficiency, mice with conditional deletion of c-Rel in Treg cells develop signs of inflammation with age, and c-Rel-deficient Treg cells are unable to control pathogenic T cells in a T cell transfer colitis model [ 26 ], demonstrating a role for c-Rel in Treg cell–mediated immune control. This was also observed in cell transfer experiments which showed that c-Rel knockout Treg cells are deficient in controlling the expansion of wild-type T cells in lymphopenic hosts [ 22 ]. Along the same line, conditional ablation of c-Rel in Treg cells affects a distinct set of genes (around 300 are up- and 350 downregulated) [ 26 ].…”
Section: Canonical Nf-κb Transcription Factors and Treg Cell Functionmentioning
confidence: 71%
“…C-Rel employs multiple mechanisms to promote the differentiation as well as thymic and peripheral functions of Treg cells in mice [ 10 , 22 , 23 ]. Indeed, c-Rel can currently be considered as the NF-κB members with the most profound effects on Treg cell biology (see Fig.…”
Section: Canonical Nf-κb Transcription Factors and Treg Cell Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…To find out the functional significance of transcription factor c-Rel downregulation in SM + M, M, and SM Tregs, we reasoned that if c-Rel is critical in promoting Treg generation and suppressive function, Rel deficiency in Tregs will lead to downregulation of significant numbers of genes in Tregs. Through our search in NIH-NCBI GeoDatasets database, we found that an Australian group published a paper on RNA Seq datasets from c-Rel deficiency (KO) in Tregs (GSE154166) [ 105 ]. We found that 35 genes were shared by the downregulated gene list from SM + M Tregs and the downregulated gene list from c-Rel knockout (KO) Tregs ( Figure 7 K).…”
Section: Resultsmentioning
confidence: 99%
“…After CD4SP thymocytes initiate strong TCR signaling in the medulla, the thymocyte-intrinsic pathways required to prevent deletion change as the thymocyte matures. Canonical NF-κB activation prevents deletion within the Foxp3 – T-reg precursor stage ( 22 , 87 89 ), whereas IL-2 signaling prevents deletion at a later stage, close to the time of Foxp3 upregulation ( 75 ). DOCK8 inhibits deletion at both of these stages ( 90 ).…”
Section: Impact Of Thymocyte Deletion In the Medulla On T-reg Selectionmentioning
confidence: 99%